Access to schooling in west bengal: A geo-social analysis - Jhuma Halder; Lakshmana, C.M. (Bengaluru)
Education is indisputably the most important indicator of social development and human prosperity. The level of prosperity of a nation depends upon the level and quality of education imparted to its citizens. Access to education is universally accepted as
Keywords: Development Studies